2020
DOI: 10.1158/1078-0432.ccr-19-4137
|View full text |Cite
|
Sign up to set email alerts
|

A20 and RBX1 Regulate Brentuximab Vedotin Sensitivity in Hodgkin Lymphoma Models

Abstract: Although there has been great progress in treating Hodgkin lymphoma (HL), the survival rate for patients diagnosed at an advanced stage or with relapsed/refractory disease remains low. The current understanding of the biology of the disease has been translated into the development and FDA approval of the first effective targeted therapy for relapsed/refractory HL, Brentuximab Vedotin (BV), a drug-conjugated anti-CD30 antibody. However, many patients do not achieve complete remission and develop BV-resistant di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…S5E), in line with previous reports describing histological EBV detection associated with older HL patients 51 and fewer mutations in TNFAIP3 34 . Also, our observation may be related to the notion that EBV-infected B-cells rely on NFkB for survival 52 . In contrast to previous reports 14, 33 , we detected no association between mutational burden and EBV in our cohort (6.0 vs. 7.3 mutations/Megabase (Mb), EBV+ vs. EBV-, p=0.3418).…”
Section: Resultssupporting
confidence: 52%
“…S5E), in line with previous reports describing histological EBV detection associated with older HL patients 51 and fewer mutations in TNFAIP3 34 . Also, our observation may be related to the notion that EBV-infected B-cells rely on NFkB for survival 52 . In contrast to previous reports 14, 33 , we detected no association between mutational burden and EBV in our cohort (6.0 vs. 7.3 mutations/Megabase (Mb), EBV+ vs. EBV-, p=0.3418).…”
Section: Resultssupporting
confidence: 52%
“…Linear Ubiquitin Chain Assembly Complex Is Essential for Supporting the Viability of A20 Mutant HL Lines Revealed by an E3 Ligase CRISPR Screen. To achieve a comprehensive understanding of how the ubiquitination pathway regulates HL pathogenesis, we produced a unique ubiquitin regulator-focused single-guide RNA (sgRNA) library for CRISPR library screens (18). This library covers around 10 sgRNAs per gene that are directed at 5â€Č constitutive exons of ∌800 human genes, including all E3 ligases, deubiquitinating enzymes, and controls.…”
Section: Resultsmentioning
confidence: 99%
“…This trial suggested the potential benefit of BV and pembrolizumab combination therapy in patients who are heavily pretreated. Nonetheless, some patients will ultimately develop BV resistance and may partially attribute to the upregulation of NF-kappaB [ 50 ] or multidrug resistance pump (MDR1) [ 51 ]. The combination therapy of BV and cyclosporine A (an MDR1 inhibitor) was recently examined in a phase I trial (NCT03013933) to combat BV resistance in cHL, which reported an ORR of 75%, a CR rate of 42%, and a modest toxicity profile [ 51 ].…”
Section: Adcs Approved For Lymphomamentioning
confidence: 99%